EFFECTIVENESS OF A VIRTUAL EDUCATION PROGRAM IN ENHANCING LEARNING INTENTION AMONG NURSING STUDENTS IN INDONESIA: A PILOT STUDY - Nurhasanah, Aisah; Hayati, Suci Noor (Jurnal Keperawatan PPNI Jawa Barat, 2025)
Objective: This study aimed to examine the effect of a virtual education intervention using video on learning intention among undergraduate nursing students. Methods: A quasi-experimental study with a two-group pretest-posttest design was conducted involving 60 undergraduate nursing students. Participants were selected using a convenience sampling method and divided equally into intervention and control groups (30 students each). Learning intention was measured using the Attention, Relevance, Confidence, Satisfaction (ARCS) scale. Data were analyzed using a paired sample t-test to determine differences in learning intention before and after the intervention. Results: A total of 60 students participated, with a mean age of 20 years (SD ± 6.56), and 84% were female. The mean learning intention score in the intervention group increased significantly from 118.63 (SD ± 9.14) before the intervention to 132.77 (SD ± 7.91) after the intervention. The difference was statistically significant (t = 0.000, p < 0.05), indicating a positive impact of the virtual education program using video on students’ motivation and intention to learn. Conclusion: The use of video-based virtual education demonstrates potential as an effective strategy to enhance learning intention among nursing students. Given its promising results, this approach could be integrated into nursing education to support student engagement and motivation. However, future research should adopt more rigorous experimental designs and larger, more diverse samples to validate and generalize these findings.